PENGARUH MOTIVASI KERJA DAN DISPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. TRANSMEDIA MAMPANG JAKARTA SELATAN - Rizki Pratama, Muhamad; Noviyanti, Iis (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of work motivation on employee performance at PT. Transmedia Mampang South Jakarta, to determine the influence of work discipline on employee performance at PT. Transmedia Mampang South Jakarta and to determine the influence of work motivation and work discipline simultaneously on employe performance at PT. Transmedia in South Jakarta. The sampling technique used a saturated/census sampling formula, so the population in this study was 62 people. The sample used was 62 respondents using questionnaire data collection techniques. The nature of the research used is quantitative descriptive. The data analysis methods used include validity testing, reliability testing, classical assumption testing, product moment correlation testing, simple linear regression, multiple regression equations, coefficient of determination testing, and hypothesis testing. Based on the research results, the influence of work motivation on employe performance shows the results of the tcount test = 2.894 while ttable = 2.000 (tcount > ttable) with a significance level of 0.013 < 0.050, the influence of work discipline on employe performance shows the test results tcount = 3.005 while ttable = 2.000 (tcount > t table) with a significance level of 0.006 < 0.050, and the influence of work motivation and work discipline on employe performance shows the test results Fcount = 1.821 while Ftable = 3.15 (Fcount > Ftable) with a significance level of 0.001 < 0.050. The multiple regression equation is Y = 25.555 + 0.308X1 + 0.043X2+ e. The multiple correlation coefficient is 0.241, which means it has a low relationship. The coefficient of determination test was 15.8% and the remaining 84.2% was influenced by other variables.